2016
DOI: 10.3850/s2382581216000053
|View full text |Cite
|
Sign up to set email alerts
|

New records of Orchidaceae from Bali, Indonesia

Abstract: During plant inventory work in the forested areas of Mt Mesehe and Mt Merbuk, Jembrana district, Bali, twenty orchid species were collected. Among the species collected, five were confirmed as new records for Bali. The five newly recorded species are Calanthe zollingeri Rchb.f., Plocoglottis plicata (Roxb.) Ormerod, Podochilus serpyllifolius (Blume) Lindl., Styloglossum speciosum (Blume) T.Yukawa & P.J.Cribb, and Vanilla albida Blume. Descriptions of taxa and images are provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Notes: e presence of this species was recorded by Sulistiarini et al (2016). It has been found on Mt Merbuk (Jembrana Regency, Bali) in an open area within a lowland forest at an altitude of 400-600 m. In 2018, on the way to Pura Pucak, Mt Batukaru, we found representatives of this species at an altitude of 1,007 m, despite it not being in flower at the time (vouchers in Ach.…”
Section: Nervilia Concolormentioning
confidence: 80%
“…Notes: e presence of this species was recorded by Sulistiarini et al (2016). It has been found on Mt Merbuk (Jembrana Regency, Bali) in an open area within a lowland forest at an altitude of 400-600 m. In 2018, on the way to Pura Pucak, Mt Batukaru, we found representatives of this species at an altitude of 1,007 m, despite it not being in flower at the time (vouchers in Ach.…”
Section: Nervilia Concolormentioning
confidence: 80%
“…Schuiteman et al (2008) mentioned that about 200 orchids species in 72 genera occur in Lesser Sunda Island and 66 species of which occur in East Timor (Silveira et al 2008). Sulistiarini et al (2016) have found 20 orchids species in Mount Mesehe and Mount Merbuk in Bali with an altitude range between 200-1.600 m asl. While Girmansyah et al (2013) have listed 146 orchids species in Bali.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, the genus Dendrobium belongs to the subfamily Orchidoideae, which has over 880 genera and more than 33,000 species distributed nearly worldwide (Chase et al., 2015; Christenhusz & Byng, 2016; Hassler, 2022; Pridgeon et al., 2014). The genus Dendrobium is one of the three largest orchid genera (comprising Bulbophyllum, Dendrobium , and Epidendrum ) (Schuiteman, 2011). It is a very large genus, containing more than 1800 species (Lam et al., 2015).…”
Section: Introductionmentioning
confidence: 99%